Analisis Aplikasi C-Acces Dalam Meningkatkan Kepuasaan Pengguna Kereta Commuterline Secara Online: (Studi Kasus Pada Kereta Commuterline Indonesia Di Wilayah Jabodetabek) - Lesmana, Budi; Sakti Muda Nasution; Mira Ismirani Fudsyi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
Indonesia Commuterline Train is a passenger transportation service between urban areas and surrounding cities such as Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi). Commuterline Train or commonly called Krl is one of the most popular modes of transportation among urban communities. For that, PT KCI created an innovation that can improve Commuterline train services by creating an application that makes it easier for every customer who uses this transportation service to fulfill their wishes. Indonesian Commuterline Train created the C-Acces application, an online application used to access train schedules using a cellphone. This application is intended to improve user efficiency and convenience in accessing Indonesian Commuterline train services. This study aims to analyze the extent to which the C-Acces application makes it easier for users when they are outside the station. This research method uses a quantitative approach by distributing questionnaires to 200 Commuterline customer respondents. The results of this analysis will show the advantages of the C-Acces application with several features that we can open such as online ticket purchases, top up multitrip card (KMT) balances, view train schedules, view train positions, monitor station density and registration of pregnant women's pins are the main factors for customer satisfaction. This study concludes that C-Acces plays a very important role in increasing customer satisfaction and making it easier for Commuterline users to access various things they need.